The Practice and Potential of Agroforestry in the Southeastern United States - Sarah W. Workman; Samuel C. Allen (EDIS)
The purpose of this instructional document—officially called a white paper—is to help farmers, landowners, extension professionals and policymakers develop solutions to some of the problems they or their clients face, using agroforestry as a land management tool. This will be done by presenting readers with the various opportunities available in agroforestry, based on a review of current and potential practices in the southeastern United States. This document is Circular 1446, one of a series through the Center for Subtropical Agroforestry (CSTAF), School of Forest Resources and Conservation, Institute of Food and Agricultural Sciences, University of Florida. First Published: June 2004.